한국 청소년의 성별에 따른 식습관, 주관적 체형 인지 및 체중 조절 행동 조사 연구 - 제 6차 청소년건강행태온라인조사를 중심으로 - 김미현; Kim, Mi-Hyun (東아시아食生活學會誌, 2012)
This study was conducted to investigate the eating habits, self-perception of body image, and weight control behavior in Korean adolescents by gender. Data pertaining to 70,809 subjects(male 37,090, female 33,719) were obtained from the sixth Korea Youth Risk Behavior Web-based Survey(2010). The rate of skipping breakfast was 42.5% in male, and 45.8% in female students. The intake frequency of vegetable, milk, soda, fast food, and instant noddles was higher in male than female students. Moreover, 33% of male and 31.9% of female students considered themselves to be somewhat or very obese. Notably, 2.3% of underweight students considered themselves to be obese. Weight control measures were practiced in 44.6% of male, and 54.6% of female students. Meal restrictions were used more frequently to control weight by females, while exercise was used more by males. The perceived stress level was higher in female than male students, especially that due to appearance. Therefore, integrated and personalized high school nutrition programs according to gender should be implemented to establish proper body image perception and eating habits, as well as to develop selfesteem.